2021
DOI: 10.3389/fnut.2021.793862
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Antioxidant Defence Status Is Associated With Metabolic-Inflammatory Risk Factors in Preterm Children With Extrauterine Growth Restriction: The BIORICA Cohort Study

Abstract: Introduction: An impaired antioxidant status has been described during foetal growth restriction (FGR). Similarly, the antioxidant defence system can be compromised in preterm children with extrauterine growth restriction (EUGR). The aim of this prospective study was to evaluate the antioxidant status in prepubertal children with a history of prematurity without FGR, with and without EUGR, compared to a healthy group.Methods: In total, 211 children were recruited and classified into three groups: 38 with a his… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…Maintaining a 10-year follow-up is difficult and especially within a group of preterm patients without EUGR and other comorbidities. Given that EUGR and reference groups exhibited the greatest differences during prepuberty stage [ 27 , 28 , 29 ], comparisons between these extreme groups were more appropriate, not considering a third and small group of preterm without EUGR.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Maintaining a 10-year follow-up is difficult and especially within a group of preterm patients without EUGR and other comorbidities. Given that EUGR and reference groups exhibited the greatest differences during prepuberty stage [ 27 , 28 , 29 ], comparisons between these extreme groups were more appropriate, not considering a third and small group of preterm without EUGR.…”
Section: Discussionmentioning
confidence: 99%
“…Perinatal clinical data and personal and family health records were collected from the clinical history of both groups, as published previously [21,22]. The median GA for EUGR participants at birth was 29.5 weeks (interquartile range (IQR) [25][26][27][28][29][30][31][32]. An extended physical exploration was conducted for all participants by the research physician.…”
Section: Clinical History Physical Examination and Blood Pressure Mea...mentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, fetal membrane CAT activity correlated with head circumference and birth weight. Ordóñez-Díaz et al [100] associated extra uterine growth restriction with an impaired antioxidant defense status. Similarly, Karowicz-Bilinska et al [101] and Luo et al [102] demonstrated that IUGR is associated with greater placental ROS and oxidative injury.…”
Section: Oxidative Stress and Fe Cu And Zn Concentrationsmentioning
confidence: 99%
“…Determination of plasma antioxidants (retinol, β-carotene, and α-tocopherol). Plasma concentrations of retinol, β-carotene, and α-tocopherol are determined by solvent extraction and ultrahigh-pressure liquid chromatography coupled to mass spectrometry (UHPLC-MS) as reported elsewhere [158,159].…”
Section: Evaluation Of the Antioxidant Defense Systemmentioning
confidence: 99%